Near real-time total grain size distributions of explosive eruptions at Mount Etna (Sicily) - Valentin Freret-Lorgeril; Costanza Bonadonna; Lorenzo Guerrieri; Simona Scollo; Luigi Mereu; Stefano Corradini; Frank Silvio Marzano (Bulletin of Volcanology, 2026)

Remote sensing measurements of fresh volcanic ash during the Mount Etna emission of February 21, 2019 - Salvatore Spinosa; Antonella Boselli; Luigi Mereu; Giuseppe Leto; Ricardo Zanmar Sanchez; Simona Scollo (Remote Sensing Applications: Society and Environment, 2025)

Constraining proximal grainsize distribution of tephra from paroxysmal eruptions at Etna volcano - Francesco Amadio; Laura Pioli; Simona Scollo (Journal of Volcanology and Geothermal Research, 2024)

Correction to: The European Volcano Observatories and their use of the aviation colour code system - Sara Barsotti; Simona Scollo; Giovanni Macedonio; Alicia Felpeto; Aline Peltier; Georgios Vougioukalakis; Elske de Zeeuw van Dalfsen; Lars Ottemöller; Adriano Pimentel; Jean-Christophe Komorowski; Susan Loughlin; Rita Carmo; et al. (Bulletin of Volcanology, 2024)

A fast compilation of the VONA messages using a computer-assisted procedure - Pietro Bonfanti; Stefano Branca; Carmelo Cassisi; Mauro Coltelli; Michele Prestifilippo; Simona Scollo (Bulletin of Volcanology, 2024)
Mt. Etna, in Italy, is one of the most active volcanoes in the world, producing several explosive events in recent years. Those eruptions form high eruption columns that often reach the top of the troposphere (and sometimes even the lower part of the stratosphere) and create several disruptions to air traffic, mainly to the Fontanarossa International Airport in Catania, which is about 20 NM (~ 37 km; NM = Nautical Miles) away from the summit craters and is located in the main wind direction. In Italy, the institution responsible for volcano monitoring is the Istituto Nazionale di Geofisica e Vulcanologia (INGV). In 2007, the INGV, Osservatorio Etneo (INGV-OE) in Catania was appointed as “State Volcano Observatory” (SVO) and, in 2014, sent the first Volcano Observatory Notice for Aviation (VONA) message. Since that moment, several VONA messages have been sent, mainly due to the high frequency of Etna activity. In order to facilitate and speed in the generation and the dispatch of the VONA messages, a computer-assisted procedure has been designed and built to help the work done by the volcanologist on duty and by the two shift workers of the 24/7 Control Room of INGV-OE. Consequently, information on the explosive activity can be quickly provided to the Volcanic Ash Advisory Center (VAAC) in Toulouse and national air traffic offices, reducing risks to aviation operations. In this work, we describe how the computer-assisted procedure works, addressing the main advantages and possible improvements. We retain that a similar approach could be easily applied to other volcano observatories worldwide.

The European Volcano Observatories and their use of the aviation colour code system - Sara Barsotti; Simona Scollo; Giovanni Macedonio; Alicia Felpeto; Aline Peltier; Georgios Vougioukalakis; Elske de Zeeuw van Dalfsen; Lars Ottemöller; Adriano Pimentel; Jean-Christophe Komorowski; Susan Loughlin; Rita Carmo; et al. (Bulletin of Volcanology, 2024)
Volcano observatories (VOs) around the world are required to maintain surveillance of their volcanoes and inform civil protection and aviation authorities about impending eruptions. They often work through consolidated procedures to respond to volcanic crises in a timely manner and provide a service to the community aimed at reducing the potential impact of an eruption. Within the International Airways Volcano Watch (IAVW) framework of the International Civil Aviation Organisation (ICAO), designated State Volcano Observatories (SVOs) are asked to operate a colour coded system designed to inform the aviation community about the status of a volcano and the expected threats associated. Despite the IAVW documentation defining the different colour-coded levels, operating the aviation colour code in a standardised way is not easy, as sometimes, different SVOs adopt different strategies on how, when, and why to change it. Following two European VOs and Volcanic Ash Advisory Centres (VAACs) workshops, the European VOs agreed to present an overview on how they operate the aviation colour code. The comparative analysis presented here reveals that not all VOs in Europe use this system as part of their operational response, mainly because of a lack of volcanic eruptions since the aviation colour code was officially established, or the absence of a formal designation as an SVO. We also note that the VOs that do regularly use aviation colour code operate it differently depending on the frequency and styles of eruptions, the historical eruptive activity, the nature of the unrest, the monitoring level, institutional norms, previous experiences, and on the agreement they may have with the local Air Transport Navigation providers. This study shows that even though the aviation colour code system was designed to provide a standard, its usage strongly depends on the institutional subjectivity in responding to volcano emergencies. Some common questions have been identified across the different (S)VOs that will need to be addressed by ICAO to have a more harmonised approach and usage of the aviation colour code.

Settling-driven gravitational instabilities associated with volcanic clouds: new insights from experimental investigations - Simona Scollo; Costanza Bonadonna; Irene Manzella (Bulletin of Volcanology, 2017)

Representivity of incompletely sampled fall deposits in estimating eruption source parameters: a test using the 12–13 January 2011 lava fountain deposit from Mt. Etna volcano, Italy - Daniele Andronico; Simona Scollo; Antonio Cristaldi; Maria Deborah Lo Castro (Bulletin of Volcanology, 2014)

Volcanic ash detection by GPS signal - Massimo Aranzulla; Flavio Cannavò; Simona Scollo; Giuseppe Puglisi; Giuseppina Immè (GPS Solutions, 2013)

Determination of the largest clast sizes of tephra deposits for the characterization of explosive eruptions: a study of the IAVCEI commission on tephra hazard modelling - Costanza Bonadonna; Raffaello Cioni; Marco Pistolesi; Chuck Connor; Simona Scollo; Laura Pioli; Mauro Rosi (Bulletin of Volcanology, 2013)

Monitoring Etna volcanic plumes using a scanning LiDAR - Simona Scollo; Antonella Boselli; Mauro Coltelli; Giuseppe Leto; Gianluca Pisani; Nicola Spinelli; Xuan Wang (Bulletin of Volcanology, 2012)